G-protein coupled receptors: hormone membrane receptors - Sealfon, Stuart (Henry Stewart Talks, 2007)
Rhodopsin: prototype GPCR, Major classes of GPCRs: rhodopsin-like, glucagon-like, mGlu-like, Experimental approaches to study GPCR structure, Rhodopsin crystal structure, GPCR activation, Signal trafficking, Receptor RNA processing/isoforms, GRKs/arrestin, Rhodopsin dimerization, RAMPs: receptor activity modifying protein, RAMPs, heterodimers and expression, GPCRs and disease, Thyroxine and thyrotropin
Archived at 2020/08/13